Identifying the potential for a comprehensive literature review service at the Institute of Oncology Ljubljana (Journal of EAHIL, 2018)
The number of systematic reviews and other types of reviews published worldwide to assist in clinical decisionmaking is increasing rapidly. A large number of these studies point to the need for expert searching as anopportunity for librarians to develop a literature review search service as a key medical library service. The aimsof the study are to analyse the review practices at the Institute of Oncology Ljubljana (systematic) and to identifythe potential for establishing a comprehensive literature review support service. A quantitative analysis of theInstitute’s 101 systematic reviews and 534 other review articles from 4 databases shows an increasing number ofpublished articles from 2000 onwards. An analysis of 45 surveys identifies a high need for and expectation fromlibrarians’ participation in the review process and in the research/clinical team.